KAsH Score predicts long term mortality after acute myocardial - Monteiro, Joel Ponte; Sousa, João Adriano; Sousa Mendonça, Flávio; Neto, Micaela; Rodrigues, Ricardo; Gomes Serrão, Marco; Silva, Bruno; Mendonça, Maria Isabel; Faria, Ana Paula; Henriques, Eva; Drumond Freitas, António (Sociedade Portuguesa de Cardiologia, 2020)
Introduction: Complex risk scores have limited applicability in the assessment of patients with myocardial infarction (MI). In this work, the authors aimed to develop a simple to use clinical score to stratify the in-hospital mortality risk of patients with MI at first medical contact. Methods: In this single-center prospective registry assessing 1504 consecutively admitted patients with MI, the strongest predictors of in-hospital mortality were selected through multivariate logistic regression. The KAsH score was developed according to the following formula: KAsH=(Killip class×Age×Heart rate)/systolic blood pressure. Its predictive power was compared to previously validated scores using the DeLong test. The score was categorized and further compared to the Killip classification. Results: The KAsH score displayed excellent predictive power for in-hospital mortality, superior to other well-validated risk scores (AUC: KAsH 0.861 vs. GRACE 0.773, p<0.001) and robust in subgroup analysis. KAsH maintained its predictive capacity after adjustment for multiple confounding factors such as diabetes, heart failure, mechanical complications and bleeding (OR 1.004, 95% CI 1.001-1.008, p=0.012) and reclassified 81.5% of patients into a better risk category compared to the Killip classification. KAsH’s categorization displayed excellent mortality discrimination (KAsH 1: 1.0%, KAsH 2: 8.1%, KAsH 3: 20.4%, KAsH 4: 55.2%) and better mortality prediction than the Killip classification (AUC: KAsH 0.839 vs. Killip 0.775, p<0.0001). Conclusion: KAsH, an easy to use score calculated at first medical contact with patients with MI, displays better predictive power for in-hospital mortality than existing scores. © 2019 Sociedade Portuguesa de Cardiologia. Published by Elsevier Espa˜na, S.L.U. This is na open access article under the CC BY-NC-ND license
Keywords: Myocardial infarction; Prognosis; Madeira Island; Portugal; score risk; KAsH